2015
DOI: 10.1016/j.steroids.2014.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of estrogens and androgens in postmenopausal serum and plasma by liquid chromatography–mass spectrometry

Abstract: Liquid chromatography-selected reaction monitoring/mass spectrometry-based methodology has evolved to the point where accurate analyses of trace levels of estrogens and androgens in postmenopausal serum and plasma can be accomplished with high precision and accuracy. A suite of derivatization procedures has been developed, which together with modern mass spectrometry instrumentation provide investigators with robust and sensitive methodology. Preionized derivatives are proving to be useful as they are not subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
25
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 67 publications
2
25
1
1
Order By: Relevance
“…All calibrators were treated in the same way as test samples. 17,18 Serum ratio of testosterone to DHT ratio was calculated. Leptin levels were measured at eighth week of treatment with ELISA (Phoenix Pharmaceuticals/Phoenix Europe GmbH, Germany).…”
Section: Sexual Steroid Leptin and Vitd Plasma Levelsmentioning
confidence: 99%
“…All calibrators were treated in the same way as test samples. 17,18 Serum ratio of testosterone to DHT ratio was calculated. Leptin levels were measured at eighth week of treatment with ELISA (Phoenix Pharmaceuticals/Phoenix Europe GmbH, Germany).…”
Section: Sexual Steroid Leptin and Vitd Plasma Levelsmentioning
confidence: 99%
“…[14] showed that the Helix pomatia enzyme, which has both a β-glucuronidase + arylsulfatase activity, and is used quite extensively for the androgen analysis, is contaminated with 3β-hydroxysteroid dehydrogenase activity which can transform dehydroepiandrosterone into 5α-androstene-3,17-dione (AD). Considering that the levels of dehydroepiandrosterone are in the low ng/ml range [1] and the AD levels are about two orders of magnitude lower [1], even low 3β-hydroxysteroid dehydrogenase activity could lead to elevated levels of AD.…”
Section: Hydrolysismentioning
confidence: 99%
“…Other circulating forms of estrogens in postmenopausal women include methyl ether metabolites as well as β-glucuronide and sulfate conjugates. However, only the sulfate conjugates can serve as precursors (through the action of sulfatases) of the corresponding unconjugated estrogens in tissues [1]. Estradiol (E2) is one of the essential sex hormones that are required for reproduction in premenopausal women.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These assays afford good sensitivity, but often lack specificity due to the cross-reaction of the antibodies used in the assays with other steroids. The inter-laboratory variability of immunoassays has caused significant problems when interpreting epidemiologic studies [4, 6]. Another limitation of immunoassay-based methods is the reliance on single analyte-by-analyte measurement, thus multiple assays are required to measure all the metabolites from a single estrogen [7].…”
mentioning
confidence: 99%